The Trinity and the kingdom : the doctrine of God - Moltmann, Jürgen.; Kohl, Margaret (1981)
Presented not as rigid dogma, but as dynamic "contributions to theology," The Trinity and the Kingdom is designed to help readers formulate their own ideas and to prepare the way for broad and intensive theological discussion.
Trinitarian theology today -- The passion of God -- The history of the Son -- The world of the Trinity -- The mystery of the Trinity -- The kingdom of freedom.
Translation of: Trinitat und Reich Gottes.
Includes bibliographical references and index.
Keywords: Trinity; Kingdom of God